Growing and managing an entrepreneurial business - Allen, Kathleen R. (Boston : Houghton Mifflin, 1999)
This book is about: Entrepreneurial management for the twenty-first century; The nature of start-up companies; The nature of rapidly growing companies; Marketing for growth; ...
Keywords: Business; Management; Enterprises; Entrepreneurship; Industrial management; Entrepreneurship; New business enterprises -- Management; Business planning